2011
DOI: 10.1590/s1516-35982011000800025
|View full text |Cite
|
Sign up to set email alerts
|

Sugar cane treated with calcium hydroxide in diet for cattle: intake, digestibility of nutrients and ingestive behaviour

Abstract: -The objective of this work was to evaluate, in bovines, the intake and apparent digestibility of nutrients, ingestive behaviour and content of total digestible nutrients (TDN) of diets based on sugar cane treated with calcium hydroxide.It was used four cows with average body weight of 412.06 kg ± 37.3 kg. The study included inclusion of calcium hydroxide at the doses 0, 8, 16 and 24 g/kg of sugar cane in natural matter basis fed in diets with 65% of roughage and 35% on concentrate, based on dry matter (DM). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“…However, DIAS et al (2011) evaluating amounts of Ca(OH) 2 (0, 8, 16 and 24g kg -1 ) found higher point for CPI and NDFI for 8g kg -1 of lime, due to increased digestibility of dry matter. MISSIO et al (2013), on the other hand, found lower CPI, NDFI and TDNI for Nellore heifers fed with sugarcane treated with 5g kg -1 Ca(OH) 2 , which was associated to the palatability and acceptability of hydrolyzed sugarcane by animals.…”
Section: ------------------------------------------------------------mentioning
confidence: 86%
See 1 more Smart Citation
“…However, DIAS et al (2011) evaluating amounts of Ca(OH) 2 (0, 8, 16 and 24g kg -1 ) found higher point for CPI and NDFI for 8g kg -1 of lime, due to increased digestibility of dry matter. MISSIO et al (2013), on the other hand, found lower CPI, NDFI and TDNI for Nellore heifers fed with sugarcane treated with 5g kg -1 Ca(OH) 2 , which was associated to the palatability and acceptability of hydrolyzed sugarcane by animals.…”
Section: ------------------------------------------------------------mentioning
confidence: 86%
“…According to the potential as ruminant feed, as well as limitations of its use, recently the amount of research about sugarcane has been intensified aiming to improve the nutritional characteristics and decrease cut frequency of this material by treating with alkalizing agents (DIAS et al, 2011;MISSIO et al, 2012). The use of limes microprocessor enables increased storage time of sugarcane due to the improvement in aerobic stability of hydrolyzed sugarcane in relation to fresh sugarcane (DOMINGUES et al, 2011) and enable increased digestibility of the fiber fraction of forage (PIRES et al, 2010), which can benefit the production of milk (ALVES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum point for total concentration of VFA of 9.20 g of calcium hydroxide was found, presenting value of 71.92 μmol/mL of ruminal fluid, which may be related to dry matter digestibility and feed intake (Dias et al, 2011). Considering the concentration of acetic acid (9.60 g), butyric acid (9.60 g) total volatile fatty acids concentration (9.20 g) in the rumen fluid, the average value of 9.46 g/kg is found.…”
Section: Resultsmentioning
confidence: 87%
“…It is observed that the doses 8 and16 g calcium hydroxide per kg of sugar cane showed average pH between 6.68 and 6.75, which could favor the development of cellulolytic bacteria and consequently improve the digestibility of NDF (Dias et al, 2011), and, according to Vanzant et al (1990), ruminal pH below 6.7 would reduce fiber digestion. In this sense, Oliveira et al (2008) emphasized improvement in digestibility of sugar cane treated with alkaline hydrolysis, highlighting the property buffering that the roughage acquires with treatment, which provides security and stability in feed for ruminants.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation